Landskabsmaleriet er ikke uskyldigt: Om stedets betydning i Henrik Pontoppidans novellesamling "Skyer" - Blicher, Elizabeth (Pontoppidaniana, 2025)
Abstract This article presents an analysis of Henrik Pontoppidan’s short story collection Skyer (1906), focusing on the significance of the different landscapes within the narratives. It explores how the depiction of landscapes functions not merely as a backdrop, but as an active element that supports the thematic concerns of the stories. By examining the interplay between landscape and narrative, the article reveals how these descriptions illuminate the ideological tensions present in the text, offering insight into Pontoppidan’s engagement with the social and political conflicts of his time. The study argues that the landscapes in Skyer serve as both a reflection of the characters’ inner lives and as a (probably Pontoppidan´s) commentary on the broader societal shifts in Denmark during the provisional period in Denmark in the 1880s. In doing so, the article underscores the complex relationship between environment, identity, and political change in Pontoppidan’s work.